Supplementary scales for the school-age forms of the Achenbach System of Empirically Based Assessment rated by adolescents, parents, and teachers: Psychometric properties in German samples - Plück Julia; Nawab Laurence; Kamenetzka Elena; Döpfner Manfred (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology)
Based on Achenbach's school-age questionnaires, research groups have investigated supplementary scales for stress problems, obsessive-compulsive problems, sluggish cognitive tempo, positive qualities, dysregulation, autism spectrum disorders, and mania in 6–18-year-olds partly only in some of the three perspectives the Achenbach System of Empirically Based Assessment (ASEBA) provides.